THE EFFECT OF PICTURE WORD INDUCTIVE MODEL (PWIM) STRATEGY TOWARD STUDENTS’ MOTIVATION IN LEARNING VOCABULARY - Taufik Suadiyatno; Kiki Rizki Ananda (Mandala, 2019)
This study aimed to find out is there any signifiacnt effect or not Picture Word Inductive Model (PWIM) toward students’ motivation in studying vocabulary at second grade students of SMPN 2 Terara in academic year 2018/2019. This research was an experimental research (quasi-experimental with nonequivalent control group design). The population of this research was all of the second grade students of SMPN 2 Terara which consist of four classes. The samples were VIII B students’ as experimental group and VIII C students’ as control group. They were chosen by using purposive sampling technique. Experimental group was treated by using Picture Word Inductive Model (PWIM) and control group was treated by Contextual Teaching and Learning (CTL) that usually used by the teacher. The instruments that were used were vocabulary test and questionnaire. The researchers used SPSS 25 to compute the data. The results of the research were as follows: the data was analyzed using t-test. The result of the research showed that, there was positive effect of Picture Word Inductive Model (PWIM) strategy toward students’ motivation in vocabulary mastery. The result of t-test calculation showed that t-test was higher than t-table (t-test = 6,119 and t-table = 2,021) at confidence of interval 0.05 (95%), df = 23+23-2=44. Therefore, Null Hypothesis (Ho) was rejected and Alternative Hypothesis (Ha) was accepted. From the result of data analysis above, the researchers concluded that there was a significant effect of Picture Word Inductive Model (PWIM) toward students’ motivation in vocabulary mastery at second grade students of SMPN 2 Terara in academic year 2018/2019.